2015
DOI: 10.18632/oncotarget.5825
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 trigged ataxia-telangiectasia mutated activation facilitates lung cancer metastasis via MMP-3/MMP-13 up-regulation

Abstract: Our previous studies show that the phosphorylation of ataxia-telangiectasia mutated (ATM) induced by interleukin 6 (IL-6) treatment contributes to multidrug resistance formation in lung cancer cells, but the exact role of ATM activation in IL-6 increased metastasis is still elusive. In the present study, matrix metalloproteinase-3 (MMP-3) and MMP-13 were firstly demonstrated to be involved in IL-6 correlated cell migration. Secondly, IL-6 treatment not only increased MMP-3/MMP-13 expression but also augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 67 publications
3
32
0
1
Order By: Relevance
“…IL-6 reportedly prevents the initiation of lung cancer by activating the transcription factor STAT3 to regulate lung macrophages and to preserve lung homeostasis [73]. However, Jiang et al also demonstrated that IL-6 enhances the progression of lung cancer by inducing ATM phosphorylation and increasing the expression of MMP-3/MMP-13, thus enhancing cell migration and promoting the metastasis of lung tumor cells [74]. Liu et al demonstrated that IL-6 can also boost the proliferation of lung cancer stem cells by suppressing the expression of cell cycle regulators [75].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 reportedly prevents the initiation of lung cancer by activating the transcription factor STAT3 to regulate lung macrophages and to preserve lung homeostasis [73]. However, Jiang et al also demonstrated that IL-6 enhances the progression of lung cancer by inducing ATM phosphorylation and increasing the expression of MMP-3/MMP-13, thus enhancing cell migration and promoting the metastasis of lung tumor cells [74]. Liu et al demonstrated that IL-6 can also boost the proliferation of lung cancer stem cells by suppressing the expression of cell cycle regulators [75].…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6 is a multifunctional cytokine involving in inflammatory response, immune regulation, metabolism homeostasis and so on (Scheller, Chalaris, Schmidt‐Arras, & Rose‐John, ; Wolf, Rose‐John, & Garbers, ). It has been reported that IL‐6 is implicated in ovarian and lung cancer cell migration, which associates with the invasion and metastasis characteristics of cancer cells (Ferraresi et al, ; Jiang et al, ). Consistently, in our current study we found that IL‐6 treatment accelerates wound closure of podocytes, increases the numbers of migrated podocytes, and promotes the invasion of cell‐free areas in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nuclear MMP2 cleaves PARP in nucleus for the degradation to promote cell invasion [27, 31]. Nuclear MMP3 activates CCN2 gene transcription for IL-6-mediated cell migration [28, 32]. As MMP7 is associated with the malignant features of cancers [33, 34], our findings offer novel and valuable insights into understanding the functions of MMP7 in PCa as following: 1) MMP7 shuttles to nucleus without being cleaved, and it certainly deserves further investigation to elucidate the mechanisms on shuttling and the biological actions of MMP7 in nucleus of PCa cells; 2) ARF binds pro-MMP7 (~30 kDa) not active-MMP7 (~19 kDa) in nucleus, and it will be interesting to know these binding domains of MMP7 and ARF proteins; 3) Nuclear factors associated with ARF-MMP7 in nuclear compartments promote cell migration of PCa cells.…”
Section: Discussionmentioning
confidence: 99%